Shiga toxin-producing Escherichia coli (STEC) in psittacine birds: molecular characterization, phylogenetic analysis and antimicrobial susceptibility (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
Among the psittacidae bred as pets, the cockatiels (Nymphicus hollandicus), agapornis (Agapornis spp.), and budgerigars (Melopsittacus undulatus) stand out, because they keep people company, and have a colorful plumage, although the zoonotic risks are little known. Escherichia coli (E. coli) is a facultative anaerobic Gram-negative bacterium belonging to the Enterobacteriaceae family. Some E. coli pathotypes are considered as diarrheagenic, and the molecular techniques are useful in identifying the genetic traits of virulence. The agent does not belong to the microbiota of psittacidae. This study investigated the presence of STEC (diarrheagenic Shiga toxin-producing E. coli) in the feces from cockatiels, budgerigars, and agapornis.